2008
DOI: 10.1111/j.1750-3841.2008.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Preservation of Cucumbers for Bulk Storage Using Acetic Acid and Food Preservatives

Abstract: Microbial growth did not occur when cucumbers were preserved without a thermal process by storage in solutions containing acetic acid, sodium benzoate, and calcium chloride to maintain tissue firmness. The concentrations of acetic acid and sodium benzoate required to ensure preservation were low enough so that stored cucumbers could be converted to the finished product without the need to wash out and discard excess acid or preservative. Since no thermal process was required, this method of preservation would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
1
23
0
2
Order By: Relevance
“…Equation (13) shows the most appropriate form for the relationship between the fruit TSS change and wax solution concentrations at different storage temperatures. Equation (14) shows the most appropriate form for the relationship between the fruit TSS change and storage temperatures at different wax solution concentrations. The constants of these equations and coefficient of determination are listed in Table 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation (13) shows the most appropriate form for the relationship between the fruit TSS change and wax solution concentrations at different storage temperatures. Equation (14) shows the most appropriate form for the relationship between the fruit TSS change and storage temperatures at different wax solution concentrations. The constants of these equations and coefficient of determination are listed in Table 7.…”
Section: Resultsmentioning
confidence: 99%
“…However, cucumbers are among a number of tropical and subtropical crops that are sensitive to above-freezing cool temperatures. Low-temperature storage of cucumbers may induce damage associated with Chilling Injury (CI), resulting in compositional as well as in morphological (structural) and microbiological changes [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of high salt and acid waste brines are generated when these preserved vegetables are desalted or deacidified so they are suitable for use in pickled vegetable products. McFeeters (1998), Papageorge and others (2003), and Pérez‐Díaz and McFeeters (2008) have shown that peppers and cucumbers can be preserved without salt and with reduced levels of acetic acid by using calcium chloride to preserve texture and sufficient amounts of the traditional preservatives sodium metabisulfite and sodium benzoate to prevent growth of spoilage microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Tahapan yang dapat dilakukan untuk mempertahankan kualitas pikel pasca fermentasi adalah mencegah terjadinya kerusakan dan meningkatkan keamanan mikrobiawinya antara lain dengan menggunakan bahan pengawet. Natrium benzoat, asam sorbat, asam fumarat dan asam asetat dengan konsentrasi beragam, merupakan pengawet yang biasa digunakan pada pikel lobak, ketimun dan jahe (Joshi dan Sharma, 2009;Pérez-Díaz dan McFeeters. 2008;Pérez-Díaz dan McFeeters, 2010;Pérez-Díaz, 2011;Rahasti, 2008).…”
Section: Pendahuluanunclassified
“…Asam fumarat merupakan produk antara siklus Kreb, dan dilaporkan dapat menghambat pertumbuhan khamir pada pikel ketimun (Pérez-Díaz dan McFeeters, 2010;Pérez-Díaz, 2011), kapang pada roti (Abu-Ghoush dkk., 2008), Escherichia coli 0157:H7 pada cider apel (Comes dan Beelman, 2002;Chikthimmah dkk., 2003) dan mikrofl ora pada pikel yang disimpan pada keadaan dingin (Lu dkk., 2011) serta pada selada potong segar (Kondo dkk., 2006). Asam asetat yang dikombinasi sodium benzoat pada pH 3,6 atau kurang, dilaporkan dapat mencegah pertumbuhan mikroba pada ketimun yang diawetkan dalam larutan garam (Pérez-Díaz dan McFeeters, 2008).…”
Section: Pendahuluanunclassified